Heavy Metal of Cd Content in Tilapia Fish from Rawa Taliwang Lake, West Sumbawa Regency - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati , Kusmiyati (Jurnal Biologi Tropis, 2024)
The main objective of this research is: To obtain levels of the metal Cadmium (Cd) in the tissues of Tilapia Fish (Oreochromis mossambicus) caught from Lake Rawa Taliwang. The special benefit is to prevent humans from eating fish contaminated with Cd heavy metal. Research has been carried out on water bodies in Rawa Taliwang Lake. There are 2 research stations, namely in the eastern and western parts of the lake. Traps (Bubu) are used to catch fish as research samples. There were samples of 6 Mujair fish taken at each station. Next, the tilapia fish sample is placed in a plastic sample and then placed in the sample box. The tilapia fish samples were then destroyed in the UNRAM analytical laboratory, then analyzed for Cd content at the DLHK NTB Environmental Laboratory. Mujair fish muscle tissue was taken and then analyzed for Cadmium (Cd) metal content using an AAS (Atomic Absorption Spectrophotometer) tool. Concentrated HNO3 and HClO4 solutions are added to measure this heavy metal, then heated so that the solution becomes clear at a temperature range of 60-70ºC for 2-3 hours.  Next, the sample solution can be measured using AAS which utilizes an air-acetylene flame. The conclusion of this research was to find that the heavy metal content Cadmium (Cd) in the tissues of Tilapia Fish (Oreochromis mossambicus) taken from the waters of Lake Rawa Taliwang was 0.13 mg/kg (ppm).